Beyond old economy - new economy dualism: Urban embeddedness of current innovation processes - Jan Rathjen (European Regional Science Association (ERSA), 2002)
Current research on spatial embeddedness of the "New Economy" clearly demonstrates the use of diverse urban assets for the emerging branch. One frequent shortcoming is, however, a simplified idea of multimedia and internet enterprises as a counter-world to the traditional economy. We argue that the multitude of service companies dealing with Internet- and Multimedia applications should be considered as part of a comprehensive economic innovation process: Small, flexible and venturesome enterprises test new technology applications for economic purposes, sometimes successfully, sometimes without success. Future steps in this innovation process can be observed already: With increasing security about the economic use of new media technologies, more and more "traditional" enterprises integrate multimedia, internet and e-commerce in their daily work. What has been the domain of service enterprises will be more and more integrated in their former clients' corporations. Nevertheless, parts of multimedia and internet application might still require highly specialized skills, thus offering a basis for independent service companies even in the future. During the first phase of the innovation process, specific assets of the city have proved to be useful as research on urban and regional embeddedness of new media enterprises has shown. It seems as if traditional enterprises - instead of undertaking this step of innovation by themselves - have entrusted this trial-and-error process to an urban milieu, characterised by its creativity, its capacity to link diverse experts and its capacity to deal with uncertainty. Thus, an institutional choice has been made in order to externalize insecurity about the economic use of new technologies. The paper aims at linking the Schumpeterian innovation cycle approach and its application to regional development to the emergence of new media based industry and its links to the traditional economy. This approach should permit to go beyond the "new economy"-"old economy" dualism in order to reveal the underlying comprehensive innovative process. The centre of interest remains the urban and regional embeddedness of the current process, that is to say, the contribution of space to innovation. Based on case studies on the Hamburg metropolitan economy, its "new economy" and its increasing links between "new" and "old economy", we intend to illustrate the specific institutional form of the current innovation process in an urban context.
Keywords: 330